2019
DOI: 10.7124/feeo.v24.1125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plant α-tubulin amino acids playing a key role in specific binding of nitroaniline compounds

Abstract: Aim. Computational prediction of amino acid residues critical for specific binding of nitro- and dinitroaniline compounds in plant α-tubulin. Methods. Protein structure modeling (I-Tasser, Grid-computing) and ligand library preparation, molecular docking (CCDC Gold), molecular dynamics (MD, Gromacs computing in Grid). Evaluation of the amino acid ensemble associated with ligand binding based on results of MD energy perturbations of protein-ligand complex. Results. The structural model of plant α-tubulin from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“… 14 , 19 21 Meanwhile, other studies have proposed that ORYbs might be located on top of the N-loop near to the β-tubulin interface (see Figure 1 D). 22 24 Unfortunately, these proposed binding sites are found in poorly accessible regions, away from amino acids with known OR mutations or comprise several highly conserved residues between ORY-susceptible and non-susceptible organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 19 21 Meanwhile, other studies have proposed that ORYbs might be located on top of the N-loop near to the β-tubulin interface (see Figure 1 D). 22 24 Unfortunately, these proposed binding sites are found in poorly accessible regions, away from amino acids with known OR mutations or comprise several highly conserved residues between ORY-susceptible and non-susceptible organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the OR mutation data and computational results, several research groups have proposed different ORY binding sites (ORYbs) in α-tubulin of plants and protozoan parasites. Some of these groups have suggested that dinitroaniline herbicides could bind directly behind the α-tubulin N-loop (H1–S2 loop, amino acids 29–64) or close to the L-loop (S9–S10 loop, amino acids 356–373). , Meanwhile, other studies have proposed that ORYbs might be located on top of the N-loop near to the β-tubulin interface (see Figure D). Unfortunately, these proposed binding sites are found in poorly accessible regions, away from amino acids with known OR mutations or comprise several highly conserved residues between ORY-susceptible and non-susceptible organisms.…”
Section: Introductionmentioning
confidence: 99%